2016
DOI: 10.1159/000444448
|View full text |Cite
|
Sign up to set email alerts
|

Concordant Patterns of Brain Structure in Mothers with Recurrent Depression and Their Never-Depressed Daughters

Abstract: Background: A growing body of research has demonstrated that having a mother with a history of major depressive disorder (MDD) is one of the strongest predictors of depression in adolescent offspring. Few studies, however, have assessed neural markers of this increased risk for depression, or examined whether risk-related anomalies in adolescents at maternal risk for depression are related to neural abnormalities in their depressed mothers. We addressed these questions by examining concordance in brain structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Given that aberrant corticolimbic function and structure are implicated in a number of forms of psychopathology, including mood disorders, Yamagata et al posited that similarities in mother-daughter neural structure may underlie the maternal transmission of mood disorders. Consistent with this formulation, Foland-Ross et al (2016) found that daughters of mothers with a history of recurrent depression, who are at high risk for developing depression themselves, exhibited patterns of cortical thinning in bilateral fusiform gyri that mirrored cortical thinning identified in their mothers. Moreover, within the high-risk group only, mothers’ pattern of cortical thinning uniquely predicted daughters’ cortical thinning in this region.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Given that aberrant corticolimbic function and structure are implicated in a number of forms of psychopathology, including mood disorders, Yamagata et al posited that similarities in mother-daughter neural structure may underlie the maternal transmission of mood disorders. Consistent with this formulation, Foland-Ross et al (2016) found that daughters of mothers with a history of recurrent depression, who are at high risk for developing depression themselves, exhibited patterns of cortical thinning in bilateral fusiform gyri that mirrored cortical thinning identified in their mothers. Moreover, within the high-risk group only, mothers’ pattern of cortical thinning uniquely predicted daughters’ cortical thinning in this region.…”
Section: Introductionmentioning
confidence: 64%
“…In addition, we also examined the concordance between mothers’ and daughters’ neural response when preparing a motor response during the task in order to test whether effects are specific to striatal activation. Given prior literature pointing to two potential models of maternal inheritance of neural structure ( Foland-Ross et al , 2016 ; Yamagata et al , 2016 ), it was unclear whether we should expect to find a pattern of concordance that is specific to the RMD/RSK group, or that is similar across all mothers-daughter pairs. Thus, we tested these alternatives in our analyses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(A) As in Fox et al [10], heritability of behavioral and brain phenotypes can be used to compute genetic correlations in neuroimaging data to identify regions where there is shared genetic influence is common to both phenotypes. (B) As in Yamagata et al [12], neural concordance among all parent-offspring dyads as measured by correlations can be compared and sex-specific tests can be performed.…”
Section: Figurementioning
confidence: 99%
“…Foland-Ross et al compared cortical thickness measurements in two groups of mothers (depressed, nondepressed) and their nondepressed daughters (categorized accordingly as high- or low-risk) [10]. Cortical thickness in regions-of-interest (ROIs) that showed significant differences between depressed and nondepressed mothers were computed for each daughter; hierarchical linear regression with mother’s cortical thickness and risk status were then used as predictors of regional cortical thickness.…”
mentioning
confidence: 99%